Evaluation of out‐of‐pocket pay genetic testing in a publicly funded healthcare system. Issue 4 (5th January 2023) - Grant, Peter; Cook, Courtney B.; Langlois, Sylvie; Nuk, Jennifer; Mung, SzeWing; Zhang, Qian; Lynd, Larry D.; Austin, Jehannine; Elliott, Alison M.
Abstract: When genetic tests are not funded publicly, out‐of‐pocket (OOP) pay options may be discussed with patients. We evaluated trends in genetic testing and OOP pay for two publicly funded British Columbia clinical programs serving >12 000 patients/year (The Hereditary Cancer Program [HCP] and Provincial Medical Genetics Program [PMGP]) between 2015–2019. Linear and regression models were used to explore the association of OOP pay with patient demographic variables at HCP. An interrupted time series and linear and logistic regression models were used on PMGP data to examine the effect of a change in the funding body. The total number of tests completed through PMGP, and HCP increased by 260% and 320%, respectively. OOP pay increased at HCP by 730%. The mean annual income of patients who paid OOP at HCP was ≥3500 higher than in the group with funded testing ( p < 0.0001). The likelihood of OOP pay increased at PMGP before the funding body change (OR per month: 1.07; 95% CI: 1.04, 1.10); while this likelihood had an immediate 87% drop when the change occurred (OR: 0.13; 95% CI: 0.06, 0.32). Patients with higher incomes are more likely to pay OOP. Financial barriers can create disparities in clinical outcomes. Funding decisions have a significant impact on rate of OOP pay. Abstract : We evaluated trends in genetic testing and out‐of‐pocket (OOP) pay for two publicly funded clinical genetics programs between 2015–2019. The total number of tests and rates out‐of‐pocket pay increased over time. Patients with higher incomes were more likely to pay OOP. Financial barriers can create disparities in clinical outcomes.